Relatório de estágio curricular supervisionado em medicina veterinária - área de ovinocultura - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This report describes the activities monitored and developed during the Supervised Curricular Internship in Veterinary Medicine (ECSMV), which was carried out in the sheep industry, under the guidance of the Veterinarian and professor Dr. Tiago Gallina Corrêa. The ECSMV was developed at the Instituto Nacional de Investigación Agropecuaria La Estanzuela, Estación Experimental “Dr. Alberto Boerger ”(INIA La Estanzuela), located at Ruta 50 Km.11, Department of Colonia, Uruguay, under the supervision of Veterinary Technician, PhD. Georgget Banchero. The internship was carried out at the Ovine Unit, involving activities in the area of production and animal health, with monitoring of experiments and research in progress at the institution. The internship period was from February 1st to April 29th, 2016, making a total of 450 hours.
Report of supervised internship in veterinary medicine - sheep farming area
Keywords: Medicina veterinária; Ovinocultura; Ovinos veterinary; Medicine; Ovinoculture; Sheep; CNPQ::CIENCIAS AGRARIAS